Pengaruh Pembelajaran Daring Berbasis Platform Edlink Terhadap Motivasi Belajar Mahasiswa - Paulus Bang, Maya Linensi Bang; Magdalena Beatrice Sogen, Maria; Marlinda Robo, Devintha; Linensi Bang, Maya (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This community service activity aims to increase the learning motivation of sixth semester students through mentoring the use of a local online learning platform, Edlink. In facing the challenges of post-pandemic learning, Edlink is used as a medium that supports flexibility, active involvement, and independent learning management by students. This activity uses a quantitative approach with a quasi-experimental method involving 20 students and measures learning motivation based on Keller's ARCS (Attention, Relevance, Confidence, Satisfaction) model. The results of the activity show that the majority of students feel an increase in learning motivation after using Edlink, especially in terms of organizing time, independence, and active participation in online learning. Therefore, this activity recommends the wider use of Edlink in higher education environments to support interactive, effective learning processes that are oriented towards strengthening student learning motivation.